2017
DOI: 10.1007/s00256-017-2609-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body MRI, dynamic contrast-enhanced MRI, and diffusion-weighted imaging for the staging of multiple myeloma

Abstract: Magnetic resonance imaging (MRI) is the most sensitive imaging technique for the detection of bone marrow infiltration, and has therefore recently been included in the new diagnostic myeloma criteria, as proposed by the International Myeloma Working Group. Nevertheless, conventional MRI only provides anatomical information and is therefore only of limited use in the response assessment of patients with multiple myeloma. The additional information from functional MRI techniques, such as diffusion-weighted imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 131 publications
1
28
0
Order By: Relevance
“…Whereas, primarily detection and surveillance of focal-nodular medullary lesions seems to be more easily done, in case of diffuse bone marrow involvement, signal intensity changes vary considerably and overlap with those of normal bone marrow patient thus illustrating inter-individual variability, which is primarily influenced by the patient's age [11]. Both qualitative MRI-monitoring using ancillary sequences like T1-weighted (T1w) and T2w and quantitative monitoring using functional image data derived from diffusion-weighted-imaging (DWI) have been therefore, recommended [12]. However, their interpretation is challenging as signal intensity changes are subject to temporal variability and are dependent also on the amount of red and yellow marrow and treatment-related shifts between these two components [11].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, primarily detection and surveillance of focal-nodular medullary lesions seems to be more easily done, in case of diffuse bone marrow involvement, signal intensity changes vary considerably and overlap with those of normal bone marrow patient thus illustrating inter-individual variability, which is primarily influenced by the patient's age [11]. Both qualitative MRI-monitoring using ancillary sequences like T1-weighted (T1w) and T2w and quantitative monitoring using functional image data derived from diffusion-weighted-imaging (DWI) have been therefore, recommended [12]. However, their interpretation is challenging as signal intensity changes are subject to temporal variability and are dependent also on the amount of red and yellow marrow and treatment-related shifts between these two components [11].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of dynamic contrast-enhanced and diffusion imaging was shown to improve the detection rate of marrow infiltration as well as the treatment response. 43 WB-MRI was also studied in solid tumors with encouraging results in many different cancers. Examples include the bony and nodal staging of prostate cancer, 44 detection of metastatic disease in breast cancer, and in the evaluation of bone involvement in non-small cell lung cancer when combined with DWI.…”
Section: Whole-body Mrimentioning
confidence: 99%
“…A strategy to improve value of WB-MRI would be to choose sequences which provide sufficient diagnostic information in a reasonable time and remove sequences which do not add any additional diagnostic information. Recent studies have reported the utility of faster sequences in whole body protocols for MM such as Dixon MRI and diffusion weighted imaging [5,[11][12][13]. These sequences have shorter acquisition times than conventional spin echo sequences and can provide additional functional information such as disease activity or bone marrow composition.…”
Section: Introductionmentioning
confidence: 99%
“…These image types provide anatomical information comparable to conventional spin echo sequences but also allow the assessment of water and fat content of bone marrow and myeloma lesions. Dixon imaging is also recommended as a core component of imaging protocols and considered important in reducing false positive lesions on DWI [13]. Gadolinium-enhanced sequences have also been shown to be useful in the assessment of MM [14], and can be included into acquisition protocols [13].…”
Section: Introductionmentioning
confidence: 99%